Development of an E-Commerce Website for Marketing Handicrafts and Carvings Unique to Sikka Using the Agile Software Development Method as an Effort to Enhance the Local Creative Economy - Lindiana Ermilinda; Yuliana Anggreani Dua Delang Kolit; Katarina Trisanta Coo (Universitas Islam Raden Rahmat, Malang, 2026)
The need for digital marketing for local artisans in Sikka Regency is increasing, requiring the development of an e-commerce system to expand market reach and support online product promotion. This study aims to design and build an e-commerce website as a digital marketing medium for artisans. The system development was carried out using the Agile Software Development method, with implementation using the CodeIgniter framework, PHP programming language, MySQL database, and interface design based on HTML, CSS, and Bootstrap. Functional testing was carried out using blackbox testing, while usability evaluation was conducted through user experience (UX) testing. The results of the study show that all the main features work according to user needs and are considered easy to use, with a clear display and fast system response. The system was successfully deployed and used by artisans as a digital marketing medium. Maintenance is carried out iteratively to support the sustainability of the system's use. Overall, the user satisfaction test results showed a positive satisfaction level of 98% for the developed system.